Evaluating Information About Osteochondritis Dissecans Shared Across Social Media Platforms. Issue 10 (29th November 2022) - Gussner, Anna; Baskar, Danika; Rohde, Matt; Ganley, Ted; Shea, Kevin
Abstract : Background: With the rise of social media, patients are using a variety of online resources to gather information about medical conditions and connect with others for support. Osteochondritis dissecans (OCD) occurs most commonly among children and adolescents, necessitating early diagnosis and management. The purpose of this study is to evaluate content on social media about OCD to quantify the reach of information shared and themes of discussion surrounding this condition. Methods: A search was performed across Facebook, Instagram, YouTube, and TikTok using the term "osteochondritis dissecans" to identify information shared related to this topic which was then analyzed based on engagement using number of followers, posts, and/or views. Results: Facebook groups provided a forum for online support and information sharing among patients with OCD and their families. The 4 identified groups had a cumulative following of over 4000 people with posts that shared personal recovery stories, solicited treatment advice, and provided updates on patient progress. Review of related Instagram hashtags revealed over 4500 posts, many of which shared personal accounts of living with OCD. The top 5 most viewed YouTube videos collectively had over 189, 000 views and were focused on educational information about OCD, relevant surgical techniques, and pertinent anatomy. The top 3 OCD-related TikTok hashtags had over 4 million total views centered on factual knowledge and sharing changes before and after surgical treatment. Conclusion: Patients with OCD and their families seek information about their condition and treatment on online sources including social media. Although social media provides a supportive community to share and receive advice, the quality of information shared in these groups is a subject for concern. Increasing physician involvement and awareness of the information shared across social media platforms may improve accuracy of information and content available to patients. Clinical Relevance: It is important for physicians treating patients with OCD to be aware of all sources of information and support, including content shared on social media as these platforms allow for the sharing of personal stories, recommendations for treatment, and educational content.